MALAYALAM CINEMA DURING THE COVID-19 PANDEMIC: EXPLORING THE SEMIOTICS OF NARRATIVE TRENDS - Thomas, Ajeesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The article explores the symbiotic relationship between cinema and technological advancements, underlining the substantial impact of these advancements on both the artistic and technical aspects of filmmaking. It underscores that innovations in areas such as cinematography, recording techniques, lighting, and post-production editing have led to profound changes in the cinematic landscape. These changes not only manifest in the creation and presentation of films but also significantly influence the audience's perceptual and experiential dimensions. Moreover, the article emphasizes that cinema functions as a reflection of societal and cultural paradigms, embodying principles from aesthetics and semiotics. It posits that cinema is not solely a medium for storytelling but also serves as a canvas upon which the aesthetics and semiotic interpretations of different time periods are portrayed. The discussion extends to the impact of the COVID-19 pandemic on the social and cultural dynamics, thereby contributing an additional layer to the examination of how cinema adapts and asserts its influence in this context. In this milieu, the pandemic has compelled filmmakers to explore alternative digital platforms, prompting a reevaluation of Malayalam cinema from both a creative and semiotic perspective. This article strives to engage in a comprehensive exploration of these intricate interactions, aiming to shed light on the multifaceted relationship between cinema and technological progress.